A case of leprosy in Malawi. Making the final push towards eradication: a clinical and public health perspective. Issue 1 (December 2016) - Roe, Cieron; May, Lucy
Abstract Statistically speaking, Malawi has achieved the World Health Organisation's target for the elimination of leprosy (<1 case per 10 000 people), yet the disease is still considered a leading cause of long term physical disability. In this case study the authors discuss the presentation of a 39-year-old gentleman to a district hospital in Malawi with multibacillary, lepromatous leprosy. The condition was initially managed in the community as an 'allergy' which suggests that local barriers currently hinder the detection of leprosy in this developing primary care system. Leprosy is a multi-system disease and this gentleman demonstrated evidence of lepromatous orchitis. Promoting an awareness of these systemic manifestations will increase the the detection of complications and circumvent long term morbidity. Efforts to optimise systems of detection, management and public and professional education are essential to drive eradication in these at-risk populations. At an international level, we must strive to fulfil the objectives outlined by the 'Enhanced Global Strategy for Further Reducing the Disease Burden due to Leprosy for 2011–2015'. At a national level, local research should delineate community factors that impede the eradication of leprosy. Developing new diagnostic and epidemiologic tools, more efficacious chemoprophylactic regimens and vaccination for endemic regions would facilitate these efforts.